2016
DOI: 10.1111/pere.12163
|View full text |Cite
|
Sign up to set email alerts
|

Perceived parent and friend support for romantic relationships in emerging adults

Abstract: Positive close relationships with immediate close network members are associated with healthy adjustment among emerging adults (EA). These influence the initiation and maintenance of romantic relationships. A cross-sectional study (N = 630) explored the role of perceived parental and friend support for the current romantic relationship in relationship quality among early EA (EEA; 18-21 years) and middle EA (MEA; 22-25 years) heterosexuals. Structural equation modeling results showed that in EEA, greater friend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 56 publications
0
26
0
1
Order By: Relevance
“…Moreover, intimate relationships which do not enjoy social support from external friends and family networks are also less satisfactory (Le, Dove, Agnew, Korn, & Musto, 2010), and a lack of this external social support becomes an additional source of stress which spills over into the relationship and can lead to instability and breakup (Felmlee, 2001;Sprecher & Felmlee, 2000). As Rodrigues, Lopes, Monteiro, and Prada (2017) recently showed, social support for relationships might be especially important for emerging adults, and early and middle emerging adults even differ in how much family vs. friends are important as sources of social support for their relationship commitment and stability. Investigating sources and the impact of social support on stress processes in intimate relationships in emerging adulthood seems to be a promising avenue for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, intimate relationships which do not enjoy social support from external friends and family networks are also less satisfactory (Le, Dove, Agnew, Korn, & Musto, 2010), and a lack of this external social support becomes an additional source of stress which spills over into the relationship and can lead to instability and breakup (Felmlee, 2001;Sprecher & Felmlee, 2000). As Rodrigues, Lopes, Monteiro, and Prada (2017) recently showed, social support for relationships might be especially important for emerging adults, and early and middle emerging adults even differ in how much family vs. friends are important as sources of social support for their relationship commitment and stability. Investigating sources and the impact of social support on stress processes in intimate relationships in emerging adulthood seems to be a promising avenue for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the role of social referents in young adults' romantic relationships has increasingly received attention. Many studies have provided evidence that social network members play an important role in the life of romantic dyads (Blair & Holmberg, 2008;Blair & Pukall, 2015;Bryan, Fitzpatrick, Crawford, & Fischer, 2001;Felmlee, 2001;MacDonald, Marshall, Gere, Shimotomai, & Lies, 2012;Rodrigues, Lopes, Monteiro, & Prada, 2017;Sinclair et al, 2014;Sinclair et al, 2015;Sprecher & Felmlee, 1992). Social networks can influence the establishment of a romantic relationship (Wright & Sinclair, 2012), its progression (Sinclair et al, 2014;Sinclair et al, 2015), and its dissolution (Felmlee, 2001;Felmlee et al, 1990;Parks & Adelman, 1983;Sprecher & Felmlee, 1992.…”
Section: Social Network Effectmentioning
confidence: 99%
“…Social network approval for romantic relationships has been operationalized in several ways, including perceived and actual network approval (Etcheverry et al, 2008;Felmlee, 2001) and approval from both sides of family and friends (Felmlee, 2001;MacDonald et al, 2012;Parks et al, 1983;Sinclair et al, 2015;Sprecher & Felmlee, 1992). With only a few exceptions (e.g., the debated "Romeo and Juliet effect"; , studies have revealed that individuals who perceived social approval for their romantic relationship reported more positive relational outcomes, such as higher levels of relationship quality (Sinclair et al, 2014;Sprecher & Felmlee, 1992), commitment (Besikci et al, 2016;Rodrigues et al, 2017;Sinclair et al, 2014;Sinclair et al, 2015), and stability (Felmlee, 2001;Sprecher & Felmlee, 1992). Longitudinal research has indicated that, in contrast, perceived social network disapproval is an important predictor of relationship breakup rate over time (Felmlee, 2001;Felmlee et al, 1990;Parks & Adelman, 1983;Sprecher & Felmlee, 1992.…”
Section: Social Network Effectmentioning
confidence: 99%
“…Friends assume an essential part in affecting the beginning and maintenance of a romantic relationship, especially in adolescence (Furman & Buhrmester, 1992;Etcheverry, Le, & Charania, 2008;Etcheverry, Le, & Hoffman, 2013). As development processes are not determined merely by age, friends may remain in their role as a main source of support until the early period of emerging adulthood (Rodrigues, Lopes, Monteiro, & Prada, 2016). On the other hand, there is evidence that parental support helps to improve adjustment, not only socially, or in terms of well-being, but also in a romantic relationship (Le, Dik, & Barbara, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In one study conducted in the United Kingdom (UK), they classified emerging adult participants into two categories based on their chronological age, which were early emerging adults (EEA; 18-21 years old) and middle emerging adults (MEA; 22-25 years old) (Arnett & Schwab, 2012;Arnett, 2015;Rodrigues et al, 2016). Other than age difference, it was argued that there was a difference in the perceived adult status between these two groups: the majority of EEAs perceive themselves as not yet having entered or having partially entered adulthood, whereas the majority of MEAs perceive themselves as having achieved adulthood.…”
Section: Introductionmentioning
confidence: 99%